Atherosclerotic Plaque Stability Is Affected by the Chemokine CXCL10 in Both Mice and Humans - Dolf Segers; Jonathan A. Lipton; Pieter J. M. Leenen; Caroline Cheng; Dennie Tempel; Gerard Pasterkamp; Frans L. Moll; Rini de Crom; Rob Krams (International Journal of Inflammation)
Background. The chemokine CXCL10 is specifically upregulated during experimental development of plaque with an unstable phenotype. In this study we evaluated the functional consequences of these findings in mice and humans. Methods and Results. In ApoE-/- mice, we induced unstable plaque with using a flow-altering device around the carotid artery. From week 1 to 4, mice were injected with a neutralizing CXCL10 antibody. After 9 weeks, CXCL10 inhibition resulted in a more stable plaque phenotype: collagen increased by 58% (P=0.002), smooth muscle cell content increased 2-fold (P=0.03), while macrophage MHC class II expression decreased by 50% (P=0.005). Also, the size of necrotic cores decreased by 41% (P=0.01). In 106 human carotid endarterectomy specimens we found that increasing concentrations of CXCL10 strongly associate with an increase in atheromatous plaque phenotype (ANOVA, P=0.003), with high macrophage, low smooth muscle cell, and low collagen content. Conclusions. In the present study we showed that CXCL10 is associated with the development of vulnerable plaque in human and mice. We conclude that CXCL10 might provide a new lead towards plaque-stabilizing therapy.